Boxes fabricated from plate-stabilized liquid marbles. Issue 14 (23rd June 2021) - Fujiwara, Junya; Yokoyama, Ai; Seike, Musashi; Vogel, Nicolas; Rey, Marcel; Oyama, Keigo; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji
Abstract : Boxes containing functional materials are fabricated from plate-stabilized liquid marbles via the evaporation of the inner liquid. Abstract : Polyhedral liquid marbles were fabricated using hydrophobic polymer plates in the shape of a circle, a heart and a star as a stabilizer and water as an inner liquid phase. Boxes could be fabricated by the evaporation of the inner water from the liquid marbles. The fabrication efficiency and stability of these boxes as a function of the plate shape were investigated. Functional materials such as polymers and colloidal particles were successfully introduced into the boxes.